Epidemiological assessment of onchocerciasis in previously unmapped villages for ivermectin distribution in Fer-Fer District, Somali Regional State, Eastern Ethiopia - Dek Kahin Yosef; Barwaqo Saleban Awil; Ahmed Saeed Ismail; Mohamed Ahmed Hassan (BMC Infectious Diseases)
Abstract Background Onchocerciasis is endemic to parts of Ethiopia; however, epidemiological data are lacking in some regions. This study aimed to assess the prevalence, intensity, and risk factors of onchocerciasis in previously unmapped villages in the Fer-Fer District of the Somali Regional State, Eastern Ethiopia. Methods A cross-sectional study was conducted between March and October 2023, with 422 participants aged ≥ 15 years, comprising 299 males (70.85%) and 123 females (29.15%). Skin snip biopsies were performed to detect and quantify Onchocerca volvulus microfilariae infection. Clinical examination and questionnaires were used to assess onchocerciasis-related skin diseases and their associated risk factors. Descriptive statistics, and logistic regression, analyses were performed. Results The overall prevalence of onchocerciasis was 19.19% (81/422). The mean microfilarial intensity was 11.11 mf/mg of skin with a community microfilarial load of 1.506 mf/mg. Onchocerciasis-related skin diseases were observed in 25.59% of participants, with pruritus (17.29%) being the most common. Females had higher infection rates than males (AOR = 1.794, 95% CI: 1.081–2.975, p = 0.023). Age > 43 years (AOR = 9.27, 95% CI: 1.59-53.832, p = 0.013) and living within 3 km of rivers (AOR = 2.05, 95% CI: 1.221–3.443, p = 0.007) were associated with a higher infection risk. Knowledge of onchocerciasis was low (15.88%) and preventive practices were limited, with 93.33% not taking any preventive action. Conclusion This study revealed a significant onchocerciasis burden in the Fer-Fer District, highlighting the need for expanded control efforts. Findings on prevalence, risk factors, and community knowledge gaps provide crucial baseline data to inform targeted interventions including mass drug administration, vector control, and health education. Further research is needed to monitor the impact of interventions and to explore innovative strategies for community engagement in onchocerciasis control. Clinical trial number Not applicable.